2001
DOI: 10.1002/jmv.2068
|View full text |Cite
|
Sign up to set email alerts
|

New genome type of adenovirus serotype 19 causing nosocomial infections of epidemic keratoconjunctivitis in Japan

Abstract: Twelve strains of adenovirus serotype 19, isolated from cases of epidemic keratoconjunctivitis in Japan in 1992, 1993, 1997, and 1998, were analyzed by DNA restriction analysis, using restriction endonucleases BamHI, BglI, BglII, EcoRI, HindIII, KpnI, PstI, SacI, SalI, SmaI, and XhoI. Among these 11 restriction endonucleases, EcoRI, PstI, SacI, and SmaI were discriminative enzymes, showing restriction patterns different from those reported previously for the prototype and the variant 19a. This new genome type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…8,24,33,[49][50][51] Our data reported demonstrated conclusively that clinical EKC isolates with an HAdV-D19 hexon gene are distinct from HAdV-D19p. Furthermore, we showed that a lack of corneal tropism for the prototype HAdV-D19 likely is due to its inability to infect human corneal epithelium, a requisite first step in adenovirus keratitis.…”
Section: Discussionmentioning
confidence: 71%
“…8,24,33,[49][50][51] Our data reported demonstrated conclusively that clinical EKC isolates with an HAdV-D19 hexon gene are distinct from HAdV-D19p. Furthermore, we showed that a lack of corneal tropism for the prototype HAdV-D19 likely is due to its inability to infect human corneal epithelium, a requisite first step in adenovirus keratitis.…”
Section: Discussionmentioning
confidence: 71%
“…The pathogenesis of these isolates was not clear. EKC typically is caused by one of three HAdV-D serotypes, HAdV-8, HAdV-19, or HAdV-37, and these strains frequently cause nosocomial outbreaks (29,(34)(35)(36). These viruses originally were isolated from patients with EKC in 1951EKC in , 1955EKC in , and 1976.…”
Section: Discussionmentioning
confidence: 99%
“…Four types, AdV3, AdV4, AdV8 and AdV37, were prototype strains, and were provided by the ATCC. AdV type 19a (AdV19a) was a clinical strain [34]. AdV19a is frequently associated with epidemic keratoconjunctivitis, whereas prototype of AdV19 (AdV19p) is not responsible for outbreaks of keratoconjunctivitis [37].…”
Section: Virusesmentioning
confidence: 99%